Character Education Builds AI Ethics, Digital Independence in Vocational Students - Radif Khotamir Rusli; Zahra Khusnul Lathifah; Warizal Warizal (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2025)
This study investigates how character education influences the development of digital independence and ethical awareness among students at SMK Amaliah as they engage with AI-powered learning environments. As reliance on AI tools like ChatGPT increases, concerns about academic integrity, critical thinking, and ethics have arisen. The research aims to create strategies for blending character education into vocational training, helping students use AI responsibly, maintain academic honesty, and build independent problem-solving skills. Employing a mixed-method approach, the study combines surveys of 200 students with qualitative analysis of character education initiatives within Islamic education. The quantitative data sheds light on students’ AI usage habits and their ethical understanding, while the qualitative aspect evaluates how character education programs influence responsible digital behavior. Findings reveal that although 75% of students use AI tools for academic tasks, only 40% have a clear grasp of plagiarism and ethical AI use. Character education plays a key role in fostering honesty, responsibility, and autonomous learning, reducing automation bias and uncritical AI reliance. This is because students involved in structured ethical discussions and guided AI use develop greater awareness of digital ethics and critical thinking. Additionally, character education encourages accountability and self-regulation by integrating moral reasoning with technological skills, ensuring students do not depend solely on AI-generated content without personal intellectual engagement. The study highlights the importance of embedding AI ethics into vocational curricula and training teachers to strengthen digital literacy and ethical decision-making. Its findings support educational practices that prepare students to handle AI responsibly and uphold academic integrity.